Karakterisasi Elastisitas Karet Alam dari Castilla elastica melalui Uji Tarik Beban Bertahap - Sufilman Ely; Frandy Akyuwen; Ruth Meisye Kaloari (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2025)
This study aims to test the elasticity properties and calculate the elastic modulus (Young's modulus) of natural rubber produced by Castilla elastica trees that grow naturally in Hila Village, Ambon Island. This plant is an alternative source of rubber that has not been widely utilized in Indonesia. The research was conducted using quantitative experimental methods in a laboratory where sap from the Castilla elastica tree was tapped, dried, and formed into uniform-sized rubber strips. Elasticity tests were carried out by applying gradual loads to each sample and measuring the increase in length due to strain. The results showed that rubber from Castilla elastica has high tensile strength but a relatively low elastic modulus, ranging from 5,416 to 16,263 N/m². This value is significantly lower than the elastic modulus of natural rubber from Hevea brasiliensis, which typically ranges between 0.32–0.42 MPa. The decrease in modulus with increasing load indicates the non-linear elastic behavior of the material. These results suggest that rubber derived from Castilla elastica is soft and has potential applications in lightweight elastic products. These characteristics indicate its potential utilization as a base material for the fabrication of lightweight elastomeric products such as flexible protective membranes, elastic adhesive coatings, soft sleeves or gaskets, and lightweight vibration-damping pads in mechanical systems.